Effects of massively multiplayer online roleplaying games on psychological health and inter-personal relationships of the male youth: A cross-sectional study in sub-urban Kolkata, West Bengal, India - Mukherjee, Soumabrata; Mallick, Akash; Biswas, Subir (Anthropological Review, 2021)
Gaming related experiences and addictive behaviours are emerging causes of adverse psycho-social health such as depression, anxiety, in adolescents and young adults around the world. Nonetheless, there remains a dearth of information relating to adolescents and young adults in India, a country which has millions of gamers.Present study examined the effects of massively multiplayer online role-playing games on the psychological health and inter-personal relationships of adolescents and young male adults of sub-urban Kolkata, West Bengal, India.Questionnaires were used to collect data on socio-economic and lifestyle traits, psychological health and inter-personal relationships were obtained from both gamers (n = 150) and non-gamers (n = 150). Data on gaming experiences and addiction were obtained only from gamers. MANCOVA and linear regression were performed to understand the effects of socio-economic and lifestyle traits, gaming experience and addiction traits on psychological health and inter-personal relationships of gamers.Study findings revealed that both gamers and non-gamers derived from a similar age group (mean age = 19.94 years) and socio-economic cluster. Disparities in psychological health in terms of depression, anxiety and stress and inter-personal relationship in terms of parent and peer attachments were present across social groups and between gamers and non-gamers. Various problematic gaming experiences and gaming related addictive behaviours resulted in poor psychological health and inter-personal relationship with parents and peers.Male gamers were at high risk to develop adverse psychological health and poor inter-personal relationships with parents and peers due to problematic gaming experience and gaming addiction. Proper education and counselling regarding the beneficial and detrimental sides of gaming may ensure better psycho-social health of adolescents and young adults in India.